-(6a+8)-5(a-7)=

Simple and best practice solution for -(6a+8)-5(a-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(6a+8)-5(a-7)= equation:


Simplifying
-1(6a + 8) + -5(a + -7) = 0

Reorder the terms:
-1(8 + 6a) + -5(a + -7) = 0
(8 * -1 + 6a * -1) + -5(a + -7) = 0
(-8 + -6a) + -5(a + -7) = 0

Reorder the terms:
-8 + -6a + -5(-7 + a) = 0
-8 + -6a + (-7 * -5 + a * -5) = 0
-8 + -6a + (35 + -5a) = 0

Reorder the terms:
-8 + 35 + -6a + -5a = 0

Combine like terms: -8 + 35 = 27
27 + -6a + -5a = 0

Combine like terms: -6a + -5a = -11a
27 + -11a = 0

Solving
27 + -11a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + -11a = 0 + -27

Combine like terms: 27 + -27 = 0
0 + -11a = 0 + -27
-11a = 0 + -27

Combine like terms: 0 + -27 = -27
-11a = -27

Divide each side by '-11'.
a = 2.454545455

Simplifying
a = 2.454545455

See similar equations:

| x+(3x)+(x+7)=63 | | gf(x)=70 | | ax=-bc | | -9(1-2y)=18y-9 | | p-22=-30 | | -(3x+5)=6x | | -20-5+x=x | | (x^2)+400=625 | | B+5=3b+9 | | 7x+48=x+48 | | 0.3(9.9)= | | e-34=681 | | 7x-17=2x | | 9x-32=x-56 | | sin60=.5/x | | b-160=23 | | 6(x-72)-4(x+64)=64-6(x-72) | | 7x-36=x+24 | | 3x+2=4x+16 | | d=20(10) | | 5x+30=6x+26 | | 3x-2=6x+9 | | 18x+6x=300-150 | | 6(x-75)-4(x+64)=64-6(x-72) | | d=50(5) | | -(x-4)=2(5x+9) | | 9x-(215/3)=4x | | 2x+8+52+5x=180 | | x-2y=14-x-3y=-9 | | 4(2x+8)=-39+23 | | (88-75)+g=50 | | 5x+2x+3x=180 |

Equations solver categories